Sowing Density Effect on Common Bean Leaf Area Development. Issue 5 (1st September 2016) - Ricaurte, Jaumer; Clavijo Michelangeli, Jose A.; Sinclair, Thomas R.; Rao, Idupulapati M.; Beebe, Stephen E.
Abstract : Sowing density is a major management factor that affects growth and development of grain crops by modifying the canopy light environment and interplant competition for water and nutrients. While the effects of density and plant architecture on static vegetative and reproductive growth traits have been explored previously in common bean ( Phaseolus vulgaris L.), there are no reports of intensive measurements of the temporal dynamics on node addition and leaf area development. Such results are reported here from two sites of field experiments where the effects of sowing densities (5, 10, 15, 20, 25, and 35 plants m −2 ) and genotypes with contrasting plant architectures (two each from growth habits I, II, and III) were assessed. Analysis of the phyllochron (°C node −1 ) indicated genotype and density effects (but no interaction) on the rate of node addition. While significant, these differences amounted to <2 d of leaf development at either site. In terms of leaf area development, analysis using a power function reflected large differences in the dynamics and final size of individual plant leaf area (PLA) between the lower density (<15 plants m −2 ) treatments and commonly used values (>20 plants m −2 ) at the growth habit but not genotype level. These differences in node addition and leaf development dynamics translated to marked differences among growth habits and densities in estimated leaf area indices and, consequently, in the estimated fraction of intercepted light at lower densities.